Factors that influence food choices in secondary school canteens: a qualitative study of pupil and staff perspectives - Devine, Lauren D.; Gallagher, Alison M.; Briggs, Stephen; Hill, Alyson J. (Frontiers in Public Health, 2023)
Adolescence is recognised as a period of nutritional vulnerability, with evidence indicating that UK adolescents' have suboptimal dietary intakes with many failing to meet dietary recommendations. Additionally, adolescence is a time of transition when they become more independent in their dietary choices and begin to develop their own sense of autonomy and are less reliant on their parentsparent's guidance, which is reported to lead to less favourable dietary behaviours. Reducing the prevalence of poor dietary intakes and the associated negative health consequences among this population is a public health priority and schools represent an important setting to promote positive dietary behaviours. The aim of this schoolbased study was to explore the factors and barriers which influence food choices within the school canteen and to identify feasible strategies to promote positive dietary behaviours within this setting. Thirteen13 focus groups with 86 pupils in Year 8 (n=37; aged 11-12 years) and Year 9 (n=49; aged 12-13 years) in 6 secondary schools across Northern Ireland, UK were conducted. Additionally, one-to-one virtual interviews were conducted with 29 school staff (principals/ vice-principals (n=4); teachers (n=17); caterers (n=7)) across 17 secondary schools and an Education Authority (EA) senior staff member (n=1). Education Authority (EA) Head of a catering (n=1). Focus groups and interviews were audio-recorded, transcribed, and analysed following an inductive thematic approach. Results Findings of this research were interpreted using the ecological framework which identified the complexity of multiple factors which influenced pupils' selection of food items in the school canteen at the individual (e.g. time/ convenience), social (e.g. peer influence), physical (e.g. food/ beverage placement) and macro environment (e.g. food provision) level. Additionally Ssuggestions for improvement of food choices which were low-cost and non-labour intensive were also identified at each ecological level: individual (e.g. rewards), social (e.g. pupil-led initiatives), physical (e.g. labelling) and macro environment (e.g. whole-school approaches). Therefore, low-cost and non-labour intensive feasible and practical strategies could be employed, for example, menu and labelling strategies, placement of foods, reviewing pricing policies and whole-school initiatives in developing future dietary interventions to positively enhance adolescents' food choices in secondary schools.